Equivalence Problem Solvability in Gateway Program Models - R. I. Podlovchenko; A. E. Molchanov (Моделирование и анализ информационных систем, 2014)
Algebraic program models with procedures are designed to analyze program semantic properties on their models called program schemes. Liberisation and equivalence problems are stated for program models with procedures. A subclass of program models with procedures called special gateway models is investigated. A better complexity algorithm for the liberisation in such models is proposed. Primitive program schemes are defined as a subclass of special gateway models. It is shown that the equivalence problem in such models is decidable if the equivalence problem is decidable in special program models without procedures. For some cases of decidability the complexity is evaluated.